Case Report: Reactive T-cell large granular lymphocytes in the bone marrow of a patient with relapsed/refractory multiple myeloma receiving teclistamab - Dean, Erin A.; Yang, Li-Jun; Seifert, Robert P.; Wingard, John R. (Frontiers in Oncology, 2025)
T-cell engager therapies for the management of relapsed/refractory (R/R) multiple myeloma (MM) may lead to neutropenia with or without associated infections, which can limit treatment and efficacy. We present a case of a patient with penta-class R/R MM who, while receiving teclistamab, developed persistent severe to moderate neutropenia with associated infections. A review of her bone marrow confirmed the eradication of the malignant plasma cells, but flow cytometry identified an increase in T-cell large granular lymphocytes (T-LGLs). Upon further analysis, T-LGLs were found to be reactive and non-clonal, ruling out secondary T-LGL leukemia. This case describes the evolving peripheral blood cell counts, bone marrow composition, and radiologic findings due to the activation of the patient’s immune system before, during, and after treatment with teclistamab. To our knowledge, this is the first reported potential association of T-LGL activation with teclistamab treatment.